A comparison of enrichment media for the isolation of salmonellae from seagull cloacal swabs. - Fricker, C. R. (Cambridge University Press, 1983)
The relative efficiency of three selective enrichment broths (Muller-Kauffmann tetrathionate. Rappaport's and selenite F) was investigated for the isolation of salmonellae from seagull cloacal swabs. Pre-enrichment in buffered peptone water was employed throughout the study, which involved the examination of 560 gulls, sixty (10.7%) of which were found to be carrying salmonellae. Rappaport's broth as modified by Vassiliadis for incubation at 43 degrees C (Vassiliadis et al. 1976) yielded the highest number of positive swabs (57) and the widest range of serotypes. It was significantly more efficient that either selenite F or tetrathionate broth, although the results obtained with Rappaport's broth incubated at 37 and 43 degrees C did not differ significantly (P greater than 0.5). Eleven serotypes were isolated during the study, the most prevalent being Salmonella virchow.